2006
DOI: 10.2223/jped.1568
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weekly treatment with ferrous sulfate on hemoglobin level, morbidity and nutritional status of anemic infants

Abstract: Objective: To evaluate the impact of weekly treatment with ferrous sulfate on hemoglobin level, morbidity and nutritional status in a sample of anemic infants from Zona da Mata Meridional in the state of Pernambuco, Brazil.Methods: A controlled, community-based intervention was carried out with 378 infants who were followed-up for 18 months. Hemoglobin level was measured at 12 months in a total of 245 children randomly selected. Participating infants were divided into three groups: two received 45 mg of elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Gera and Sachdev reviewed several trials and found that iron supplementation increases the risk of developing diarrhea by 0.05 more episodes per year, which is considered a low risk [33]. Similar to other studies [34,35], this study did not find a difference in diarrhea episodes among treatments.…”
Section: Discussionsupporting
confidence: 83%
“…Gera and Sachdev reviewed several trials and found that iron supplementation increases the risk of developing diarrhea by 0.05 more episodes per year, which is considered a low risk [33]. Similar to other studies [34,35], this study did not find a difference in diarrhea episodes among treatments.…”
Section: Discussionsupporting
confidence: 83%
“…20 Prevention of anaemia due to whatever aetiology will reduce the incidence of LRTI. 19 Most studies could not find any relation between the prevalence of anaemia and length of hospitalisation. The length of hospital stay may be related to other factors such as the severity of the disease, presence of other complications and care.…”
Section: Discussionmentioning
confidence: 98%
“…Lima et al reported a higher prevalence of anaemia in infants with infectious diarrhoea. 19 Ramkrishna K et al studied haemoglobin level as a risk Factor for Lower Respiratory Tract Infections and identified anaemic children were 5.75 times more prone to lower respiratory infections compared to the control group. 20 Prevention of anaemia due to whatever aetiology will reduce the incidence of LRTI.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, IDA is a major health problem, and its occurrence varies between 40% and 60% among children less than 2 years old [2][3][4] ; among children with anemia aged between 12 and 16 months, 95% have iron deficiency 2 .…”
mentioning
confidence: 99%
“…Because it is a lowcost treatment, has high absorption and solubility, and improves the nutritional status quickly, this preventive treatment starts at an early age. Iron supplements are well tolerated by most infants, have no measurable effect on body growth in children, and early iron supplementation, even in breastfed infants, is feasible and transiently increases iron status 4 . FS has been analyzed in several studies in dentistry [5][6][7][8][9][10][11][12][13] using artificial dental models (mainly bovine teeth and human permanent teeth).…”
mentioning
confidence: 99%